Inhibition of CRM1 reverses hypoxia-driven chemoresistance in acute myeloid leukemia via overcoming HIF-1α-mediated lysosomal sequestration - Feng, Xiaohui; Ding, Yuntian; Huang, Yuling; Qin, Hancheng; Wang, Xiaobo; Zeng, Yunxin (Frontiers in Immunology, 2025)
IntroductionIn relapsed/refractory acute myeloid leukemia (R/R-AML), hypoxia-driven chemoresistance is orchestrated by HIF-1α-induced P-glycoprotein (P-gp) overexpression and subsequent lysosomal sequestration of anthracyclines. Nuclear-cytoplasmic shuttling of the HIF-1α prolyl-hydroxylase PHD2 is controlled by chromosome region maintenance 1 (CRM1), which is frequently up-regulated in AML; however, whether pharmacologic CRM1 inhibition restores PHD2 nuclear availability to accelerate HIF-1α degradation and reverse chemoresistance remains undefined.MethodsAML cell lines (MV4–11 and MOLM13) were cultured under normoxic or hypoxic conditions. The effects of hypoxia on drug sensitivity, intracellular drug distribution, and protein expression were assessed using CCK-8 assays, immunofluorescence, Western blot, and flow cytometry. Genetic and pharmacological inhibition of P-gp, HIF-1α, and CRM1 was performed to validate their roles in chemoresistance. Hypoxia-adapted zebrafish CHT xenografts were employed for in vivo validation.ResultsHypoxia reduced AML cell sensitivity to DNR, increased HIF-1α and P-gp expression, and promoted lysosomal sequestration of DNR. Inhibition of P-gp or HIF-1α reversed these effects. CRM1 and PHD2 expression increased under hypoxia, but nuclear accumulation of PHD2 decreased. Selinexor restored PHD2 nuclear localization, promoted HIF-1α degradation, reduced P-gp expression, and enhanced DNR nuclear accumulation. Combination treatment with Selinexor and DNR significantly increased apoptosis and DNA damage in vitro and reduced leukemia burden in zebrafish xenografts.ConclusionsCRM1 inhibition by Selinexor re-establishes nuclear PHD2 residency, increases the degradation of HIF-1α in hypoxia, abrogates P-gp-mediated lysosomal anthracycline trapping, and confers potent in-vitro and in-vivo chemosensitization. These data provide mechanistic rationale for integrating Selinexor into salvage regimens for R/R-AML.